Analysis of Religious Values as the Foundation of a Simple Life among the Bajo Community - Taheriah, Nuragifah; Salam, Shinta Nurhidayati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The life of the Bajo community is inseparable from the sea, characterized by simplicity and guided by religious values, specifically Islam, which is the faith of the Bajo people in Indonesia. According to data from the Central Bureau of Statistics, the religious composition in Indonesia consists of 87.2% Islam. This study examines the simple lifestyle of the Bajo community as a manifestation of religious values in their daily lives. The research was conducted in Bajo settlements in Kelurahan Bajoe, Kecamatan Tanete Riattang Timur, Kabupaten Bone, and Desa Samabahari, Kecamatan Kaledupa, Kabupaten Wakatobi. The study employed both primary and secondary data. Data collection techniques included literature review and field studies through direct interviews. Data were analyzed qualitatively. The analysis reveals that the simplicity of the Bajo community is closely related to the living norms within their society. These include religious norms manifested in contentment with what they have; moral norms reflected in maintaining traditions while upholding religious values; norms of courtesy demonstrated through hard work and mutual respect, fostering social harmony; and legal norms, evidenced by living within their means and avoiding excess. In conclusion, simplicity in the life of the Bajo community is not merely a lifestyle but represents a deeply rooted religious value that permeates every aspect of their existence. It ensures balance in their relationship with nature, fellow humans, and God in the utilization of marine resources.